From parent to 'peer facilitator': a qualitative study of a peer‐led parenting programme. (28th March 2014) - Thomson, S.; Michelson, D.; Day, C.
Abstract Background Peer‐led interventions are increasingly common in community health settings. Although peer‐led approaches have proven benefits for service users, relatively little is known about the process and outcomes of participation for peer leaders. This study investigated experiences of parents who had participated as 'peer facilitators' in Empowering Parents, Empowering Communities (EPEC), a peer‐led programme designed to improve access to evidence‐based parenting support in socially disadvantaged communities. Method A qualitative cross‐sectional design was used. Semi‐structured interviews were conducted with 14 peer facilitators and scrutinized using thematic analysis. Results Peer facilitators developed their knowledge and skills through personal experience of receiving parenting support, participation in formal training and supervised practice, access to an intervention manual, and peer modelling. Peer facilitators described positive changes in their own families, confidence and social status. Transformative personal gains reinforced peer facilitators' role commitment and contributed to a cohesive 'family' identity among EPEC staff and service users. Peer facilitators' enthusiasm, openness and mutual identification with families were seen as critical to EPEC's effectiveness and sustainability. Peer facilitators also found the training emotionally and intellectually demanding. There were particular difficulties around logistical issues (e.g. finding convenient supervision times), managing psychosocial complexity and child safeguarding. Conclusions The successful delivery and sustained implementation of peer‐led interventions requires careful attention to the personal qualities and support of peer leaders. Based on the findings of this study, support should include training, access to intervention manuals, regular and responsive supervision, and logistical/administrative assistance. Further research is required to elaborate and extend these findings to other peer‐led programmes.